Polymer-based hybrid catalyst of low Pt content for electrochemical hydrogen evolution - Chakrabartty, S. (International Journal of Hydrogen Energy, 2017)
Hydrogen is regarded as the most promising fuel to replace conventional fossil fuel. The electrochemical production of hydrogen requires catalyst and development of efficient non-Pt catalysts or catalysts with low Pt content are in demand. Herein, we demonstrate the photochemical synthesis of a hydrogen evolution electrocatalyst poly(α-terthiophene)-Pt nanoparticle hybrid material (polyTT-Pt) of low Pt content and its electrocatalytic activity. The synthesis of polyTT-Pt hybrid material involves the photoinduced electron transfer between α-terthiophene (α-TT) and and the subsequent in situ growth of polymer and Pt nanoparticles. The irradiation of the mixture of α-TT and with sunlamp initiates the oxidative polymerization and reduction of Pt complex to Pt nanoparticles. The polymer has cabbage-like microstructure and the in situ grown Pt nanoparticles have an average size of 1.8 nm. The Pt nanoparticles are embedded into the polymer matrix as well as randomly distributed over the polymer. The hybrid material contains 2.91 wt% of Pt and it shows characteristic electrochemical signature with an electrochemically active surface area of 35.7 m²/gPt. The hybrid material polyTT-Pt is electrocatalytically highly active though it contains very small amount of Pt. It efficiently catalyses hydrogen evolution reaction (HER) and the bench mark current density of 10 mA/cm² is achieved at an overpotential of 67 mV. The mass activity of the hybrid catalyst is 1172 mA/mgPt at the overpotential of 67 mV. The high activity is ascribed to the high electronic conductivity of the polymer matrix, facile access of electrolyte due to the embedded small nanoparticles and the presence of large number of catalytically active Pt sites. Tafel analysis suggests that the HER follows the Volmer-Tafel mechanism. Polymer-based hybrid catalyst of low Pt content for electrochemical hydrogen evolution. Available from: https://www.researchgate.net/publication/319039592_Polymer-based_hybrid_catalyst_of_low_Pt_content_for_electrochemical_hydrogen_evolution [accessed Oct 16 2017].